A new computer vision based method for rail track detection and fault diagnosis in railways - Karakose, Mehmet; Yaman, Orhan; Baygin, Mehmet; Murat, Kagan; Akin, Erhan (International Journal of Mechanical Engineering and Robotics Research, 2017)
Computer vision-based condition monitoring methods, the methods are increasingly used on railway systems. Rail condition monitoring process can be performed using data obtained with the help of computers using these methods. In this study, a computer-based visual rail condition monitoring is proposed. By means of a camera placed on top of the train the rail that the train is on and the neighbor rail images are taken. On these images, the edge and feature extraction methods are applied to determine the rails. The resulting several faults between railways were studied to determine if there is a failure. The results obtained are given at the end of the study. Experimental results show that the proposed method is examined, it is observed that a healthy and effective results. © 2017 Int. J. Mech. Eng. Rob. Res.
Keywords: Condition monitoring; Fault diagnosis; Image processing; Railway systems